1983
DOI: 10.1037/0278-7393.9.4.607
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between item and category learning: Evidence that abstraction is not automatic.

Abstract: Recent studies of concept formation using ill-defined categories suggest that abstraction of category-level information is more or less an automatic consequence of experience with exemplars. An experiment using ill-defined categories composed of photographs of women was designed to test this assumption. Experimental manipulations required subjects to learn either identification (exemplar level) and/ or classification (category level) responses to the photographs. Exemplar learning was generally found to procee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
1
4

Year Published

1989
1989
2005
2005

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(148 citation statements)
references
References 28 publications
6
137
1
4
Order By: Relevance
“…To our best knowledge, this is the first study in which predictions of the prototype view and of the exemplar view are compared to predict category-based decisions for natural language concepts. Our results differ somewhat from the findings in the majority of papers that have investigated category learning, where it is assumed that all previously encountered exemplars of a category are stored and are activated whenever category-related decisions have to be made (Gluck & Bower, 1988;Medin, Altom, & Murphy, 1984;Medin, Dewey, & Murphy, 1983;Medin & Schaffer, 1978;Nosofsky, 1987Nosofsky, , 1988Nosofsky, , 1991. The data presented here suggest that activation of a limited number of frequently generated exemplars of the studied concepts suffices to predict typicality ratings, response times, exemplar-generation frequencies, and category-naming frequencies significantly and that elaborating the exemplar set can even decreases the predictive power.…”
Section: Discussioncontrasting
confidence: 56%
“…To our best knowledge, this is the first study in which predictions of the prototype view and of the exemplar view are compared to predict category-based decisions for natural language concepts. Our results differ somewhat from the findings in the majority of papers that have investigated category learning, where it is assumed that all previously encountered exemplars of a category are stored and are activated whenever category-related decisions have to be made (Gluck & Bower, 1988;Medin, Altom, & Murphy, 1984;Medin, Dewey, & Murphy, 1983;Medin & Schaffer, 1978;Nosofsky, 1987Nosofsky, , 1988Nosofsky, , 1991. The data presented here suggest that activation of a limited number of frequently generated exemplars of the studied concepts suffices to predict typicality ratings, response times, exemplar-generation frequencies, and category-naming frequencies significantly and that elaborating the exemplar set can even decreases the predictive power.…”
Section: Discussioncontrasting
confidence: 56%
“…For example, Medin et al (1983) found that people are faster to associate unique names to photographs of nine female faces than they are to categorize the photographs into two categories. The logical structure of the two categories is shown in Table 3 (the logical structure of the categories is roughly equivalent to Shepard et al's Type IV problem).…”
Section: Sustain's Principles: Item Versus Category Learningmentioning
confidence: 99%
“…Learning problems requiring item memorization should be more difficult than learning problems that promote abstraction and many models of categorization are constrained to predict that categorization will be, at worst, no harder than identification. Unlike Shepard et al (1961), Medin et al (1983) used distinctive stimuli (photographs of faces) and found that identification learning was actually more efficient than classification learning. As we shall we, SUSTAIN offers an explanation for this counter-intuitive finding.…”
Section: Learning At Different Levels Of Abstractionmentioning
confidence: 99%
“…ARTMAP predicts that critical feature patterns to which humans learn to pay attention are stored in memory. Under language/cultural supervision, these prototypes can be either specific ("exemplars"; Estes 1994;Medin & Smith, 1981;Medin et al 1983) or general ("prototypes"; Posner & Keele 1970;Smith & Minda 1998;Smith et al 1997). Typically, both specific and general information will be learned ("rule-plus-exceptions" ;Nosofsky 1984;Nosofsky et al 1992;Palmeri et al 1994).…”
Section: Realistic Constraints On Brain Color Perception and Categorymentioning
confidence: 99%